Coping Stress pada Narapidana Pelaku Pembunuhan Tidak Berencana di Lembaga Pemasyarakatan Perempuan Kelas II A Semarang - Adriani Maria Salean; Maria Nugraheni Mardi Rahayu (Guidena)
Prisoners spend a certain period in prison and must live in institutions with minimal activities. The longer the punishment period, the higher the stress conditions experienced by prisoners. The purpose of this research is to describe the coping stress strategies used by the inmates of unplanned murder at the Lembaga Pemasyarakatan Perempuan Kelas IIA Semarang. This research uses qualitative methods with a case study approach. Participants in this research were selected based on the purposive sampling technique; the selected participants were three female inmates of unplanned murder at the Lembaga Pemasyarakatan Perempuan Kelas IIA Semarang who were sentenced to more than 15 years. The research found that emotion-focused coping is a stress-coping strategy used more often than problem-focused coping. This is because of the minimal resources and the conditions of the demands of punishment in the prison, making the subject unable to cope with existing stressors directly. Subjects who are stressed and able to cope with it feel relieved, glad, optimistic, happy, and more motivated to pass their period of punishment.